THE IMPLEMENTATION OF SOCIAL MEDIA AND NETWORKING AS AN EDUCATIONAL TOOL FOR HIGHER EDUCATION IN INDONESIA: THE PROMISE AND CHALLENGES - Hendrik Yohant Possumah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This article discusses the use of Social Media and Networking (SMN) as an Educational Tool for Higher Education in Indonesia. Technology has been an integral part of our life and it cannot be separated from the education sector either. This article examines the history of Social Media and Networking in altering thy way people communicate, before proceeding to examine its use in Education in general. This article will first discuss about the current situation of SMN and Higher Education (HE) in Indonesia. Definition of what SMN is and the types will be described as well. It will then present the promise and the challenges of utilizing the SMN for HE, as well as the current debates on this issue. There have been considerable discussions and debates regarding the implementation or the benefits of utilizing SMN into the education sector, especially in Indonesia. The question whether the use of SMN in education will bring more benefits than drawbacks, remains as a widely debated topic. This article will examine opinions from scholars and scholarly journals about the topic before comparing them with the context within Indonesian education sector. It will then present the promise and the challenges of utilizing the SMN for HE, as well as the current debates on this issue. Finally, some considerations and suggestions will be provided at the end of the article.